Neuromuscular Facilitating Exercises For Sensory Receptors and Their Effect On Injured Shoulder Joint Rehabilitation in Weightlifter With Special Needs - Abdul Nabi, Hamid; Kahlif, Emad (Journal of Physical Education, 2019)
Weightlifting for individuals with special needs require strength and determination through consistent and hard heavy weight training during which the lifter can experience neuromuscular cram in shoulder joint and muscle making them prone for injuries. The importance of the research lies in using neuromuscular facilitating exercises for sensory receptors to rehabilitate injured shoulder. The problem of the research was in rehabilitating shoulder joint to improve shoulder range of motion during bending and abduction. The research aimed at identifying the effect of these exercises on sensory receptors for shoulder rehabilitation in weightlifters with special needs as well as improving their shoulder's range of motion. The subjects of the research were (4) advance weightlifters with special needs. The rehabilitation sessions lasted for eight weeks with three sessions per week. The researchers concluded that neuromuscular facilitating exercises played a great role in improving shoulder range of motion. Finally the researchers recommended using these exercises for rehabilitating shoulder joint.